A COMPARISON OF SKELETAL AGE OF THALASSAEMIC PATIENTS OF 9-15 YEARS WITH CHRONOLOGICAL AGE BY RADIOGRAPHY - Imtiaz, Humaira; Akbar, Wajid; Jadoon, Omair Khan; Ali, Usman; Ambreen, Sadaf; Javed, Sumaira; Shaheen, Farkhanda; Anwar, Jamil (Journal of Ayub Medical College Abbottabad, 2019)
Background: Thalassemia is inherited disorder characterized by haemolytic anaemia, due to complete absence or reduced Î²-globin chain synthesis, stimulating pathological bone marrow overstimulation and altered erythropoiesis. The change in bone mass ultimately results into miss interpretation of bone age once assed from x-ray radiograph. The aims compare skeletal age of thalassaemic children of 9-15 years with chronological age by x-ray wrist bones. Methods: This was cross sectional analytical study; the study was conducted in conjunction with Fatimid Hospital Peshawar Pakistan and Out Patients Department (OPD) of paediatrics for minor illness (other than Thalassemia) Khyber Teaching Hospital August 2014 to January 2015. A total 156 samples were selected convenient sampling to make comparison of bone age and chronological age between thalassaemic children (age 9-15years) and age sex matched normal control. A structure data collection check list was used to collect data X-ray findings (bone age). SPSS 20 was used for statistical analysis. Results: The results showed a total of 156 children with their mean age 11.9±2.2, male were 97 (62.2%) and females 59 (37.8%). Out of thalassaemic (n=76) majority 49 (62.8%) were male as compared to female 29 (37.2%). The mean chorological age among both of group were not significantly different (p=0.67). However, the bone age was significantly different from each other (p=0001). Pearson's correlation analysis revealed that was strong correlation between erupt teeth and bone age (r=0.462, p=0.0001). Conclusions: Skeletal age assessment was found to be suboptimal along with chronological age in children and adolescents suffering from thalassemia. Keywords: Chronological age; B-Thalassemia Major; Bone age; Paediatrics; Sex matched